Load Imbalance Analysis on Low-Voltage Distribution Network: A Case Study on SM3 Feeder, Tomohon Main Substation - Kapri Benaya Alexander Rompis; Rio Carolus Junio Runtu; Nathaniel Lumalan Bijang; Arnold Robert Rondonuwu (Riviera Publishing, 2026)
Load imbalance on low-voltage distribution networks arises from the uneven distribution of single-phase loads across a three-phase system, resulting in elevated neutral currents, increased power losses, and degraded voltage quality. This research systematically analyzes the degree of load imbalance on the low-voltage distribution network of SM3 Feeder, Tomohon Main Substation, PT PLN (Persero) UP3 Manado, using phase current measurements, neutral current readings, and customer load data collected from field surveys. The methodology employed phase current measurements, neutral current readings, and customer load data collected from field surveys at five measurement points representing diverse loading conditions and network topologies. The percentage load imbalance (PLI) was calculated and benchmarked against SPLN D3.002-1:2007 and IEEE Std 1159 standards, with measurements conducted during morning, afternoon, and evening peak periods. Findings reveal significant imbalance in four of five assessed feeder segments, with the most critical level reaching 31.7% at MP-5. Elevated neutral currents produced measurable additional power losses in the neutral conductor, and customer terminal voltage violations were confirmed at MP-3 and MP-5, with the most severe deviation reaching ?9.7% below the nominal 220 V. The study concludes that systematic load redistribution at MP-5, MP-3, and MP-1, combined with mandatory phase allocation for new connections and quarterly monitoring protocols, is required to restore standard compliance and improve network efficiency, power quality, and reliability on the SM3 Feeder distribution system.